Desaın Karakter Vıdeo Game Dengan Menggunakan Vector Graphıcs: Case Study Hollow Knıght - Deli .; Rendi . (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
Vector Graphics is defined as a computer graphic image in the form of points on the Cartesian plane, served by lines and curves to form polygons and other shapes at high resolution without losing quality in its implementation in various media and visuals. The focus of this research is to examine the use of Vector Graphics elements found in one of the daily needs of electronic technology that is currently in demand in the entertainment sector in the form of video games, one of the video games that will be used as visual research on the elements found in "HOLLOW KNIGHT. The main focus of the Vector Graphics element used in the research of the Action-Adventure genre video game is the Character Design.